Intramolecular Cyclizations of Vinyl-Substituted N,N‑Dialkyl Arylamines Enabled by Borane-Assisted Hydride Transfer - Tian, Jun-Jie; Zeng, Ning-Ning; Liu, Ning; Tu, Xian-Shuang; Wang, Xiao-Chen (ACS catalysis, 2019)
Catalytic amounts of B(C6F5)3 have been found to be able to promote the intramolecular cyclization of vinyl-substituted N,N-dialkyl arylamines to afford nitrogen-containing heterocycles. Our mechanistic studies indicate the reaction is initiated by abstraction of an α-hydride from an N-alkyl substituent by B(C6F5)3, which is followed by cyclization, and is concluded by delivery of the hydride to the cyclic cationic intermediate. The dual roles of B(C6F5)3, first as an oxidant and then as a hydride-carrying reductant, have enabled a rare redox-neutral cyclization process between a sp3 carbon and an electron-rich olefin without using a transition metal or an external oxidant.